A novel crank inerter with simple realization: Constitutive model, experimental investigation and effectiveness assessment. (1st July 2022) - Zhang, Li; Xue, Songtao; Zhang, Ruifu; Hao, Linfei; Pan, Chao; Xie, Liyu
Highlights: A novel crank inerter is proposed to generate variable negative stiffness. A constitutive model is built to predict the mechanical behavior of the crank inerter. The prototype crank inerter is fabricated with a simple configuration and tested. Variable negative stiffness of crank inerter is illustrated experimentally and theoretically. The effectiveness of crank inerter is illustrated in an isolator over classic inerter. Abstract: The inerter-based device is of increasing interest to scholars in the field of structural vibration control, which is characterized by apparent mass and negative stiffness effects. With this regard, it is potential to develop variable negative stiffness characteristics with the technology of inerter, which is promising to provide improved performance for structural vibration isolation and vibration suppression. In this study, the theoretical analysis and experimental investigation of a novel inerter element, named crank inerter, is performed. The presented crank inerter is proposed to generate a variable negative stiffness effect, which is realized on the basis of a crank mechanism. A constitutive model of crank inerter is developed to predict its mechanical behavior. For an in-depth understanding of the inertial property of the crank inerter, a parametric analysis is conducted on the inertia force calculation of the crank inerter. A prototype crank inerter is fabricated and tested under sinusoidal excitations to verify the proposed constitutive model. A variable negative stiffness of the crank inerter is reflected from the proposed constitutive model. The theoretical results calculated with the proposed constitutive model match well with the experimental data, which verifies that the proposed model can predict the mechanical behavior of the crank inerter. The dynamic analysis of a vibration isolator with a crank inerter is conducted to illustrate its effectiveness using the proposed constitutive model. The analysis results preliminarily show that the isolator with crank inerter can improve the structural performances regarding the peak force transmissibility and frequency band. Based on the presented investigations, a crank inerter with a simple configuration is summarized to be effective for providing an apparent mass effect and variable negative stiffness.